Fertile bonds : Bedouin class, kinship, and gender in the Bekaa Valley - Joseph, Suzanne E. (University Press of Florida, 2013)
A portrait of a group of Bedouins in the Bekaa Valley of Lebanon, a population with the highest fertility rate in the world. Many married couples in this pastoral community are close relatives - a socially advantageous practice that reflects the deep value Bedouins place on kinship. To outsiders, such family norms can seem disturbing, even premodern. They attract assumptions of Arab "backwardness," poverty, and sexism. Astoundingly, however, this book flips these stereotypes. The author, an anthropological demographer, shows that in this particular group, prolific birth rates coincide with moderate death rates and high levels of nutrition. Despite differences in gender, class, and occupation, members of Bekaa Bedouin society rely heavily on kinship ties, sharing, and reciprocity, and experience a high degree of social and demographic equality.